HPLC-determination of active components in dietary supplement «L-CARNITINE smart» - O. D. Voitiuk; A. V. Yegorova; YU. V. Scrypynets; S. N. Kashutskуy; O. G. Kluchnik; I. V. Umetskaya (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Dietary supplements are compositions of biologically active substances intended for consumption with food or addition to food products for the purpose of optimization of metabolic processes and functions of the human body. The dietary supplements include: vitamins, trace elements, amino acids, enzymes, proteins, probiotics, oils that can provide antioxidant, detoxifying, immunomodulatory, adaptogenic effects, etc. Detection of physiologically active components in dietary supplements is a difficult task and requires the use of modern highly informative research methods. One of the most powerful and versatile methods of determination is the method of high performance liquid chromatography (HPLC), combining the selective separation of the studied mixtures and high sensitivity. The purpose of this study was to develop a simple, rapid and selective method for determining ascorbic acid and L-carnitine L-tartrate in a multicomponent dietary supplement, produced in the form of sachets, using HPLC with spectrophotometric detection. The object of the study is the dietary supplement «L-CARNITINE smart», powder for oral solution of 16 g each in a sachet (INTERСHЕM). For the quantitative determination of the applied method of high-performance liquid chromatography. Chromatography was performed on an Agilent 1260 Infinity 2D LC System (USA) liquid chromatograph with a UV detector. The optimal conditions for the analysis have been experimentally determined: the type of sorbent, the composition of the eluent and its gradient, the wavelength and the detection time for ensuring the release of all components (including auxiliary substances) from the column, selective separation of ascorbic acid, potassium acesulfame and L-carnitine L-tartrate, minimization analysis time. The method has been validated according to the following parameters: specificity, linearity, accuracy, limit of quantitation.